PENGARUH MODIFIKASI DAN OPTIMASI RANGKA TERHADAP KINERJA PADA STRUKTUR JEMBATAN RANGKA BAJA SEPANJANG - Sumaidi Wijaya; Anna Rumintang (CI-TECH, 2021)
The Sepanjang bridge is a steel frame bridge that connects Sepanjang Sidoarjo Park and Surabaya's Mastrip Road. Redesigned to determine whether with different types and shapes of frames can get a bridge that remains strong to bear the burden carried but more economical, namely by reducing the steel profile used. Analysis and modeling of the bridge structure along will be carried out using SAP2000 software. Modeling is done with the framework of existing conditions and order configuration results and configuration optimization. The result with the right configuration will provide better efficiency, so that the optimization of the steel profile reduction can be done on the Sepanjang Bridge. Keywords: